2009
DOI: 10.1007/s10745-009-9216-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Transition, Socioeconomic Differentiation, and Gender Among Adult Xavante Indians, Brazilian Amazon

Abstract: High prevalence rates of overweight and obesity are increasingly common among indigenous Amazonian societies experiencing greater involvement in market economies. An important factor in such nutritional transition is internal socioeconomic differentiation, which partially accounts for fatness frequencies. We report the results of a diachronic anthropometric comparison and crosssectional anthropometric and socioeconomic survey of Xavante adults from a single, large community. Our data show an accelerated nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1
19

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 41 publications
2
66
1
19
Order By: Relevance
“…(15) y 23% (16) . Se ha reportado que los valores culturales, como el de intercambio de alimentos entre parientes y en la comunidad, podrían tener un efecto mitigador en la evolución hacia la obesidad entre pobladores indígenas que han sido expuestos a significativos cambios socioeconómicos (16) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…(15) y 23% (16) . Se ha reportado que los valores culturales, como el de intercambio de alimentos entre parientes y en la comunidad, podrían tener un efecto mitigador en la evolución hacia la obesidad entre pobladores indígenas que han sido expuestos a significativos cambios socioeconómicos (16) .…”
Section: Discussionunclassified
“…Se ha reportado que los valores culturales, como el de intercambio de alimentos entre parientes y en la comunidad, podrían tener un efecto mitigador en la evolución hacia la obesidad entre pobladores indígenas que han sido expuestos a significativos cambios socioeconómicos (16) . En los asháninkas, sería importante investigar la contribución de las características culturales, incluyendo las redes sociales de intercambio de alimentos, la dieta y la actividad física en el desarrollo o mitigación de enfermedades crónicas como obesidad e hipertensión.…”
Section: Discussionunclassified
“…The currently available data have not allowed identifying an equivalent trend for Brazil's indigenous peoples as a whole. Even so, while precarious sanitation and difficult access to healthcare services contribute to the prevalence of infectious and parasitic diseases, studies have also pointed to increasingly high rates of non-communicable diseases (NCDs) among some Brazilian indigenous peoples 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have found an increase in blood pressure levels since contact between indigenous peoples and the non-indigenous population 4,5,9 . In addition, NCDs have increased more rapidly among indigenous peoples when compared to the Brazilian population as a whole 4,5,9,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…This persistence arose from the fact that in the 1950s and 60s the category became adopted in the public sphere more widely, including by all kinds of political agents, and featured in numerous scientific studies in areas like health or genetics itself (Santos, 1996;Little;Sussman, 2010), without mentioning evolutionary psychology. Sometimes, 'race' was mobilized in close connection with terms like population, in biological anthropology, or ethnic group, in sociocultural anthropology (Véran, 2012), as evinced in more recent works like those of Santos et al (2009), Gaspar Neto and Santos (2011) and Wade et al (2014).…”
Section: A Brief History Of International Biological Anthropologymentioning
confidence: 99%